Case 3820: Hemiarthrinae Markham, 1972 (Arthropoda, Malacostraca) and Hemiarthridae Sirenko, 1997 (Mollusca, Polyplacophora): proposed resolution of homonymy between family-group names - Schwabe, Enrico (Bulletin of Zoological Nomenclature, 2020)
The purpose of this application, under Article 55.3.1 of the Code, is to resolve the homonymy between the family-group names Hemiarthrinae Markham, 1972, with type genus Hemiarthrus Giard & Bonnier, 1887 (Arthropoda, Malacostraca), and Hemiarthridae Sirenko, 1997, with type genus Hemiarthrum Carpenter in Dall, 1876 (Mollusca, Polyplacophora). It is proposed that the Commission declare the stem of the generic name Hemiarthrum Carpenter in Dall, 1876 to be Hemiarthrum-, resulting in a change of the spelling of the name Hemiarthridae Sirenko, 1997 to Hemiarthrumidae.
Keywords: Nomenclature; taxonomy; Arthropoda; Mollusca; Malacostraca; Polyplacophora; HEMIARTHRINAE; HEMIARTHRIDAE; homonymy